Bladder dysfunction in hereditary spastic paraplegia: what to expect?. Issue 3 (2nd September 2009) - Braschinsky, Mark; Zopp, Inga; Kals, Mart; Haldre, Sulev; Gross-Paju, Katrin
Abstract : Background: Hereditary spastic paraplegia (HSP) comprises a group of rare neurodegenerative disorders characterised by progressive spasticity and hyperreflexia of the legs. Neurogenic bladder dysfunction is a well recognised problem in patients with HSP but it has not yet been described systematically in the literature. The aim of this study was to provide an evidential overview of the ways in which urinary dysfunction presents in HSP. Methods: 49 patients with HSP were included and underwent evaluation. A history was followed by a semi-structured interview and, in those patients who consented, measurement of residual volume of urine (PVR) and urodynamic evaluation. Results: 38 subjects (77.6%) reported some type of urinary symptom. Subjective complaints of bladder problems showed a correlation with verified urinary dysfunction. There were no significant differences in the occurrence of urinary disturbances between the pure and complex forms of HSP. The most frequent symptoms were incontinence (69.4%), hesitancy (59.2%), increased frequency of micturition (55.1%) and urgency (51.0%). Incomplete bladder emptying was the rarest (36.7%). The most common combination of symptoms was to have all of them (14.3%). Incomplete bladder emptying as a complaint was associated with an increased risk of PVR. Women had a higher risk of increased voiding frequency. Conclusions: To our knowledge, this work is the first systematic and disease oriented overview of neurogenic bladder disturbances in patients with HSP. Our results may be useful to the clinicians who work with HSP patients, allowing them to make appropriate screening and management decisions.